Contemporary challenges of tourism - Dejan Nakovski; Ace Milenkovski; Mijalce Gjorgievski (UTMS Journal of Economics, 2021)
Tourism is an economic activity that is very sensitive to social, economic, political and security changes. Such changes can be both positive and negative. These may be in the tourist destination or the area from where the tourists come from. The changes may affect tourists, tourism workers, travel companies, stakeholders, the domicile population, the local community, etc. Tourism in the Republic of North Macedonia is no exception and is not immune to such changes. Ongoing changes that may occur are a challenge for the entire tourism industry but also for tourist destinations when it comes to their management and development. The authors aim in the paper to present the modern challenges of tourism in the country, and to propose models and new ways of understanding the need for flexible and adaptable tourist offers that will meet the contemporary challenge.
Keywords: L83; Z32; I15; O18; 330; tourism destination; tourism offer; policy; development